Cannabis use associated with high-risk drug use among Palestinians: An emerging health risk - Basma Damiri; Saed Bilbeisi; Majdeddin MohammedAli; Mohab Najjar (Population Medicine)
Introduction The West Bank has seen an increase in cannabis use, but there are few studies on the prevalence and factors associated with tetrahydrocannabinol (THC) use among Palestinians. The aim of this study was to examine the prevalence of THC use and its associations with sociodemographic factors and its potential association with the use of alcohol, tobacco, energy drinks, coffee, and also other illicit drugs.